Strengthening Islamic Economics Tafsir Surat Al Baqoroh Verse 275 - Ahmad Zaki (Journal of Islamic Studies & Social Science, 2024)
The interpretation of Surat Al-Baqarah verse 275 on usury highlights the importance of economic understanding in Islam and the role of the Qur'an and hadith in shaping the Islamic perspective on economic practices. This article discusses the controversy surrounding usury in the context of Islamic economics and explains the views of various commentators and scholars. Usury is explained as an additional or excess payment that is prohibited in Islam because it harms one of the parties in an economic transaction. Regardless of the definition, usury is expressly forbidden in the Qur'an and hadith, with the threat of punishment for the perpetrators. This paper outlines the various tafsir methods used to understand the verses related to usury, including ijmali and tahlili methods, as well as analyzing the historical context and economic practices during the time of the Prophet and Jahiliyyah Arab society. By affirming the prohibition of usury and analyzing its laws in Islam, this article seeks to clarify the concept of usury for Muslims and offer alternative solutions, such as the profit-loss sharing system, in building an economic system that is in accordance with Islamic principles. Through a deeper understanding of usury and the principles of Islamic economics, it is hoped that Muslims can strengthen the foundations of a just and sustainable economy, in accordance with the teachings of their religion.